Calcium Sensing Receptor Inhibits Growth of Human Lung Adenocarcinoma Possibly via the GSK3β/Cyclin D1 Pathway - Li, Jiansha; Liao, Pu; Wang, Kun; Miao, Zhuangzhuang; Xiao, Rui; Zhu, Liping; Hu, Qinghua (Frontiers in Cell and Developmental Biology, 2020)
The effect of calcium sensing receptor (CaSR) on tumor cell proliferation has been studied in several human cancers, and great discrepancies were found in different tumors. However, the role of CaSR in lung adenocarcinomas (LUAD) is not clear. Therefore we investigated the function of CaSR on regulating the growth of human LUAD and its possible mechanism. The expression of CaSR protein and its relationship with pathological parameters were examined in paraffin sections from 51 LUAD patients, by immunohistochemistry. The results showed CasR expression was negatively correlated with the Ki-67 index as well as the grade of malignancy in LUAD. Further, CaSR demonstrated an in vitro inhibitory effect on the proliferation of human LUAD A549 cells by regulating CaSR activity with agonist cinacalcet, antagonist NPS2143 or shRNA-CaSR transfection. Tumor xenograft models also verified the in vivo proliferation-inhibiting role of CaSR by subcutaneous injecting A549 cells into nude mice with or without changes of CaSR activity. Molecularly, western blotting displayed CaSR positively regulated the activity of glycogen synthase kinase 3β (GSK3β), followed by the down-regulation of Cyclin D1. We used the dominant negative mutant and the constitutively active mutant plasmid of GSK3β to alter GSK3β activity. Our functional experiments showed that the proliferation- inhibition of CaSR was suppressed by the inactivation of GSK3β, and enhanced by the activation of GSK3β. These results suggested CaSR played a proliferation- inhibiting role in LUAD, at least partially by regulating GSK3β/Cyclin D1 pathway.